Applying additive manufacturing technologies to a supply chain: A Petri net-based decision model - Patalas-Maliszewska, Justyna; Wiśniewski, Remigiusz; Zhou, MengChu; Topczak, Marcin; Wojnakowski, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
Nowadays, applying additive manufacturing (AM) technologies into a supply chain (SC) permits realization of the so-called "demand chains" and transformation of conventional production to mass customization. However, integration of AM technologies within an SC indicates the need to support managers` decision about such an investment. Therefore, this work develops a Petri net-based decision support model that determines the changes in an SC by adopting AM and improving customer-perceived value (CPV), based on a case study regarding a real-life metal production process.
Keywords: additive manufacturing technology; supply chain; Petri nets; reliability; robustness; decision support systems; verification